Contribution of Lactobacillus iners to Vaginal Health and Diseases: A Systematic Review - Zheng, Nengneng; Guo, Renyong; Wang, Jinxi; Zhou, Wei; Ling, Zongxin (Frontiers in Cellular and Infection Microbiology, 2021)
Lactobacillus iners, first described in 1999, is a prevalent bacterial species of the vaginal microbiome. As L. iners does not easily grow on de Man-Rogosa-Sharpe agar, but can grow anaerobically on blood agar, it has been initially overlooked by traditional culture methods. It was not until the wide application of molecular biology techniques that the function of L. iners in the vaginal microbiome was carefully explored. L. iners has the smallest genome among known Lactobacilli and it has many probiotic characteristics, but is partly different from other major vaginal Lactobacillus species, such as L. crispatus, in contributing to the maintenance of a healthy vaginal microbiome. It is not only commonly present in the healthy vagina but quite often recovered in high numbers in bacterial vaginosis (BV). Increasing evidence suggests that L. iners is a transitional species that colonizes after the vaginal environment is disturbed and offers overall less protection against vaginal dysbiosis and, subsequently, leads to BV, sexually transmitted infections, and adverse pregnancy outcomes. Accordingly, under certain conditions, L. iners is a genuine vaginal symbiont, but it also seems to be an opportunistic pathogen. Further studies are necessary to identify the exact role of this intriguing species in vaginal health and diseases.